Ok we have the following system of equations:
![\begin{gathered} 5x+2y=18 \\ 5x-y=36 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d76yyc8196jnzxfifbw1oe6z05m24sx0pj.png)
So the first thing to do is take one of the equations above and clear either x or y. I'm going to pick the second equation and clear y:
![\begin{gathered} 5x-y=36 \\ 5x=36+y \\ 5x-36=y \\ y=5x-36 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ljuuq92aje8bygk4b7wvxf853mnapkmf7f.png)
Now we substitute this result in the first equation:
![\begin{gathered} 5x+2y=5x+2\cdot(5x-36)=18 \\ 5x+10x-72=18 \\ 15x=18+72=90 \\ x=(90)/(15)=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qq5icdxq8z87u985vsw01um9d92ev0zuma.png)
Now that we know x we take the result of clearing y from the second equation and find its value:
![\begin{gathered} y=5x-36 \\ y=5\cdot6-36=30-36 \\ y=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/oqyizmjava9ccd9ggnc01u7qddba266ccu.png)
So in the end x=6 and y=-6.